المفاهيمُ التداوليةُ في المجموعةِ القصصيةِ "مارية وربعٌ من الدائرة" لـ حسن علي البطران - سوفي, رشدي; شعيب, نوري (جامعة الوادي - University of Eloued, 2023)
وُسِمت هذه المذكرة بالمفاهيم التداولية في المجموعة القصصية "مارية وربع من الدائرة" للكاتب والقاص السعودي حسن علي البطران وقد قسمت هذه الدراسة إلى فصلين، الأول تضمن الجانب النظري تطرقنا فيه إلى التعاريف الاصطلاحية لكل مفهوم من التداولية على حدى ، ولم نأت على الخوض فيها بكامل تفاصيلها، ذلك أننا تناولناها مفاهيميا اصطلاحيا فقط وهي: (الإشاريات، الاستلزام الحواري، أفعال الكلام وفق تقسيم كل من جون أوستين وجون سيرل، ومتضمنات القول بوجهيها المتمثلان في الافتراض المسبق والقول المضمر، ثم ذكرنا أيضا عنصري القصدية والحجاج). أما الفصل الثاني فمثل الجانب التطبيقي من الدراسة، حاولنا فيه التمثيل لهذه المفاهيم التداولية بنماذج من المجموعة القصصية "مارية وربع من الدائرة" وكان لزاما منا الولوج إلى السياقات المتضمنة في الحزم القصار والطوال من هذه القصص، ولقد شرحنا هذه الأمثلة من منظور تداولي متبنين ما جاء في الكتب والمراجع من شروحات، والجدير بالذكر هو أن هذه المجموعة القصصية جاءت مرمزة ، بلغة مكثفة تحتمل العديد من التأويلات، لذلك فتطبيقنا للمفاهيم التداولية عنها كان على حسب فهمنا وتأويلنا وقد نخطأ أو نصيب. Abstract: This memorandum is marked by the deliberative concepts in the short story collection "Maria and a quarter of the circle" by the Saudi writer and storyteller Hassan Ali Al-Batran. This study was divided into two chapters, the first included the theoretical side, in which we dealt with the idiomatic definitions of each concept of pragmatics separately, and we did not come to go into it in full detail, because we dealt with it conceptually idiomatically only, namely: (signs, dialogic imperative, verbs of speech according to the division of each From John Austin and John Searle, and the contents of the saying in its two aspects represented in the presupposition and the implicit saying, then we also mentioned the elements of intentionality and arguments). The second chapter represented the applied side of the study, in which we tried to represent these pragmatic concepts with examples from the collection of stories "Maria and a quarter of the circle" and we had to access the contexts included in the short and long bundles of these stories, and we explained these examples from a pragmatic perspective, adopting what came In books and references there are explanations, and it is worth noting that this collection of stories came encoded in an intense language that bears many interpretations, so our application of the deliberative concepts about them was according to our understanding and interpretation, and we may make a mistake or a lot.
Keywords: مارية وربع من الدائرة ، الإشاريات، الاستلزام الحواري، أفعال الكلام، الافتراض المسبق، والقول المضمر ، القصدية; Maria and a quarter of the circle , signals, dialogue imperative, speech verbs, presupposition, implicit saying, intentionality.